Optimized configuration to reduce H2 carbon footprint in a refinery. (July 2022) - Leclerc, Mathieu; Rodrigues, Guillaume; Dubettier, Richard; Ruban, Sidonie
Highlights: Compared the impact of solvent (e.g. amine) versus Cryocap™ H2 cryogenic technology on CO2 emission reductions rates for hydrogen production with SMR. Assessed direct and indirect emissions for solvent (e.g. amine) and Cryocap™ H2 technologies for various electrical carbon footprint scenarios. Total CO2 emissions are reduced with Cryocap™ H2 compared to solvent technologies. CO2 emissions reduction rates for Cryocap™ H2 are higher than solvent technologies across all power grid footprint scenarios. Abstract: As hydrogen is increasingly being recognized as a critical energy vector in the energy transition, capturing CO2 from existing H2 production facilities plays a significant role towards decarbonisation. Air Liquide has industrialized an innovative technology Cryocap™ H2, combining membranes and cryogenic solutions to capture CO2 most efficiently, at the lowest cost, and at a very high purity. This paper illustrates the impact of cost-effective partial capture technology choices (e.g. amine wash versus Cryocap™ H2 ) to CO2 emission reduction rates and overall carbon footprint. Direct and indirect emissions (i.e. Scopes 1, 2, and 3) were defined for each technology choice, alongside scenarios for low, medium, and high carbon footprint environments. The paper also explores an optimization path on the CO2 emissions reduction rate using a network configuration within a refinery. The study demonstrates that with Scope 1 emissions, the partial capture net CO2 emission reduction rate is 62% with a Cryocap™ standalone, 80% with a Cryocap™ Network, but only 56% with an amine wash due to its additional requirement of steam. Analysis of all emissions Scopes illustrates that Cryocap™ 's net CO2 emissions reduction rate ranges from 52% to 66% across low, medium, to high carbon footprint scenarios, and 39% to 44% for amine wash. The advantageous case for Cryocap™ across all three Scopes remains regardless of the additional steam production method (i.e. natural gas vs electric boiler).